Pengaruh Beban Kerja, Stres Kerja, dan Job Insecurity Terhadap Turnover Karyawan - Anjasmara Putra Dinata; Suhana Suhana (IPM2KPE, 2023)
This study aims to determine the effect of workload, work stress, and Job Insecurity on employee Turnover at Pizza Hut Semarang. The population in this study were 150 employees at Pizza Hut Semarang. The number of samples to be taken in this study are 100 employees. Determining the number of samples to be used in this study by means of Quota Sampling, namely to determine samples from populations that have a high school diploma and a minimum working period of 6 months up to the desired number (quota). The data collection technique used in this study was a questionnaire. Source of data used in this research is primary data secondary data. In the data analysis test, the researcher conducted a validity test, reliability test, multiple regression test, coefficient of determination (R2), f test and t test. The results of this study show, Job Stress has an effect on Employee Turnover, and Job Insecurity has an effect on Employee Turnover, while Workload has no effect on Employee Turnover. Keywords: Workload, Work Stress, Job Insecurity, Employee Turnover